2009
DOI: 10.1111/j.1365-2966.2009.14439.x
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the obscuring torus in NGC 1068 with the power of infrared interferometry: revealing the inner funnel of dust

Abstract: We present new interferometric data obtained with mid‐infrared interferometric instrument (MIDI) for the type II Seyfert galaxy NGC 1068, with an extensive coverage of 16 uv points. These observations resolve the nuclear mid‐infrared emission from NGC 1068 in unprecedented detail with a maximum resolution of 7 mas. For the first time, sufficient uv points have been obtained, allowing us to generate an image of the source using maximum entropy image reconstruction. The features of the image are similar to those… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
273
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(306 citation statements)
references
References 50 publications
29
273
3
1
Order By: Relevance
“…Through MIR interferometric observations, Jaffe et al (2004) estimated a warm (T = 320 K) dust structure with a 2.1 pc thick and 3.4 pc diameter, surrounding a hot (T > 800 K) compact (∼1 pc) structure. Additional MIR interferometric observation by Raban et al (2009) suggested a hot (∼800 K) 1.35 pc long and 0.45 pc thick structure with a larger 3 × 4 pc and warm (T ∼300 K) dust structure at a P.A. = −42 • .…”
Section: Analysis and Discussionmentioning
confidence: 93%
“…Through MIR interferometric observations, Jaffe et al (2004) estimated a warm (T = 320 K) dust structure with a 2.1 pc thick and 3.4 pc diameter, surrounding a hot (T > 800 K) compact (∼1 pc) structure. Additional MIR interferometric observation by Raban et al (2009) suggested a hot (∼800 K) 1.35 pc long and 0.45 pc thick structure with a larger 3 × 4 pc and warm (T ∼300 K) dust structure at a P.A. = −42 • .…”
Section: Analysis and Discussionmentioning
confidence: 93%
“…Swain et al (2003) presented K-band long-baseline A&A 523, A27 (2010) interferometry of the type-1 AGN NGC 4151, which arguably resolve the innermost hot region of the dust torus (see Kishimoto et al 2007, for this interpretation). More recently, VLTI/MIDI long-baseline mid-IR spectro-interferometry directly revealed the parsec-scaled dust emission sizes in the wavelength band from 8 to 13 μm for a number of nearby type 1 and type 2 AGN (Jaffe et al 2004;Tristram et al 2007;Beckert et al 2008;Raban et al 2009;Tristram et al 2009). These observations finally confirmed the basic picture of the dust torus, while more detailed characteristics remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Reflection is associated with the reprocessing of the primary continuum by material either close to the central black hole, in the accretion disk (George & Fabian 1991;Matt et al 1991), or more distant, for example in a torus (Antonucci 1993;Jaffe et al 2004;Meisenheimer et al 2007;Raban et al 2009). A&A 567, A44 (2014) It can also be produced either in the narrow-or broad-line regions .…”
Section: Introductionmentioning
confidence: 99%